Effect of acupuncture on brain regions modulation of mild cognitive impairment: A meta-analysis of functional magnetic resonance imaging studies - Ma, Shiqi; Huang, Haipeng; Zhong, Zhen; Zheng, Haizhu; Li, Mengyuan; Yao, Lin; Yu, Bin; Wang, Hongfeng (Frontiers in Aging Neuroscience, 2022)
Objective: To conduct a meta-analysis of brain imaging studies of acupuncture-treated MCI patients to summarize the effects of acupuncture on the modulation of brain regions in MCI, and thus to elucidate the central mechanisms of acupuncture for MCI from a neuroimaging perspective. Methods: Using acupuncture, neuroimaging, magnetic resonance, and Mild Cognitive Impairment as search terms, PubMed, EMBASE, Web of Science, Cochrane Library, China National Knowledge Infrastructure (CNKI), China Biology Medicine disk (CBM disk), Wanfang and Chinese Scientific Journal Database (VIP) for brain imaging studies on acupuncture on MCI published up to April 2022. Voxel-based neuroimaging meta-analysis of fMRI data was performed using voxel-based d Mapping with Permutation of Subject Images (SDM-PSI), allowing for Family-Wise Error Rate (FWER) correction for correction multiple comparisons of results.Meta-regression was used to explore demographic information and altered cognitive function effects on brain imaging outcomes. Linear models were drawn using MATLAB 2017a, and visual graphs for quality evaluation were produced using R software and RStudio software. Results:A total of seven studies met the inclusion criteria, with 94 patients in the treatment group and 112 patients in the control group. All studies were analyzed using the regional homogeneity (ReHo) method. The experimental design of MRI included six task state studies and one resting-state study. The results showed that MCI patients had enhanced activity in the right insula, left cingulate/paracingulate gyrus, right thalamus, right middle frontal gyrus, right cingulate/paracingulate gyrus, and right middle temporal gyrus brain regions after acupuncture treatment. The MCI group showed stronger activity in the right supramarginal gyrus after acupuncture treatment compared to healthy controls. Meta-regression analysis showed that the right anterior thalamic projection ReHo index was significantly correlated with the MMSE score after acupuncture treatment in all MCI patients. Conclusions:Acupuncture therapy has a modulating effect on the brain regions of MCI patients. However, due to the inadequate experimental design of neuroimaging studies, multi-center neuroimaging studies with large samples are needed better to understand the potential neuroimaging mechanisms of acupuncture for MCI. In addition, machine learning algorithm-based predictive models for evaluating the efficacy of acupuncture for MCI may become a focus of future research.